Exploration of morpholine-thiophene hybrid thiosemicarbazones for the treatment of ureolytic bacterial infections via targeting urease enzyme: Synthesis, biochemical screening and computational analysis - Munir, Rubina; Zaib, Sumera; Zia-ur-Rehman, Muhammad; Javed, Hira; Roohi, Ayesha; Zaheer, Muhammad; Fatima, Nabiha; Bhat, Mashooq Ahmad; Khan, Imtiaz (Frontiers in Chemistry, 2024)
An important component of the pathogenicity of potentially pathogenic bacteria in humans is the urease enzyme. In order to avoid the detrimental impact of ureolytic bacterial infections, the inhibition of urease enzyme appears to be an appealing approach. Therefore, in the current study, morpholine-thiophene hybrid thiosemicarbazone derivatives (5a-i) were designed, synthesized and characterized through FTIR, 1H NMR, 13C NMR spectroscopy and mass spectrometry. A range of substituents including electron-rich, electron-deficient and inductively electron-withdrawing groups on the thiophene ring was successfully tolerated. The synthesized derivatives were evaluated in vitro for their potential to inhibit urease enzyme using the indophenol method. The majority of compounds were noticeably more potent than the conventional inhibitor, thiourea. The lead inhibitor, 2-(1-(5-chlorothiophen-2-yl)ethylidene)-N-(2-morpholinoethyl)hydrazinecarbothioamide (5g) inhibited the urease in an uncompetitive manner with an IC50 value of 3.80 ± 1.9 µM. The findings of the docking studies demonstrated that compound 5g has a strong affinity for the urease active site. Significant docking scores and efficient binding free energies were displayed by the lead inhibitor. Finally, the ADME properties of lead inhibitor (5g) suggested the druglikeness behavior with zero violation.